2016
DOI: 10.1111/all.12955
|View full text |Cite
|
Sign up to set email alerts
|

The cat lipocalin Fel d 7 and its cross‐reactivity with the dog lipocalin Can f 1

Abstract: We investigated the prevalence of sensitization to the cat lipocalin Fel d 7 among 140 cat-sensitized Swedish patients and elucidated its allergenic activity and cross-reactivity with the dog lipocalin Can f 1. Sixty-five of 140 patients had IgE to rFel d 7 whereof 60 also had IgE to rCan f 1. A moderate correlation between IgE levels to rFel d 7 and rCan f 1 was found. rFel d 7 activated basophils in vitro and inhibited IgE binding to rCan f 1 in 4 of 13 patients, whereas rCan f 1 inhibited IgE binding to rFe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 19 publications
2
46
0
2
Order By: Relevance
“…We are also aware that the results from our real-life economic study are applicable only for pollen AIT in Kazakhstan and cannot be generalized, but it has been shown for southern parts of Europe that allergen molecule-based testing would have changed AIT prescription also in these regions substantially [10,11]. So far no studies are available which have analyzed how allergen molecule-based diagnosis would affect AIT prescriptions for indoor allergen sources, but several studies have shown that molecular diagnosis is also more precise in identifying sensitizing indoor allergen sources as compared to allergen extract-based diagnosis [31,32,33]. Should further studies in different populations, regions, and different allergen sources show a similar cost-efficacy of molecular allergen-based diagnosis over allergen extract-based diagnosis for AIT prescription, molecular allergy diagnosis will become standard practice and help to reduce the continuously exploding health care costs for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We are also aware that the results from our real-life economic study are applicable only for pollen AIT in Kazakhstan and cannot be generalized, but it has been shown for southern parts of Europe that allergen molecule-based testing would have changed AIT prescription also in these regions substantially [10,11]. So far no studies are available which have analyzed how allergen molecule-based diagnosis would affect AIT prescriptions for indoor allergen sources, but several studies have shown that molecular diagnosis is also more precise in identifying sensitizing indoor allergen sources as compared to allergen extract-based diagnosis [31,32,33]. Should further studies in different populations, regions, and different allergen sources show a similar cost-efficacy of molecular allergen-based diagnosis over allergen extract-based diagnosis for AIT prescription, molecular allergy diagnosis will become standard practice and help to reduce the continuously exploding health care costs for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-specific basophil degranulation was analyzed by monitoring the basophil activation markers CD203c and CD63 as previously described 41 . Heparinized venous blood samples from four red meat-allergic patients (IgE range 5.2–>100 kU A /l against α-Gal, see Table S1) and one non-allergic individual were analyzed with BTG, α-Gal peptides obtained after 1 h of gastric phase and pepsin from porcine mucosa as control.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies tested cross reactivity in this group of allergens [8] [11] [12]. Can f 1 and Fel d 7 allergens share a 60% of identity in their amino acid sequences and cross reactivity have been demonstrated experimentally [13]. Although both allergens were part of the group B, we found only a 28% of identity between these lipocalins, a low grade of identity to expect cross-reactivity.…”
Section: Discussionmentioning
confidence: 58%